Effects on QTc Interval of 2 Different Doses of Spinal Anesthesia in Inguinal Hernia Operations - Hanbeyoglu, Onur; Urfalioglu, Aykut; Yazar, Fatih Mehmet; Ozcan, Sibel (Int Scientific Literature, Inc, 2017)
Background: Cardiac arrhythmia is a significant cause of morbidity and mortality. In this study, through examination of the effects on the QTc interval of different doses of hyperbaric bupivacaine, we investigated the relationship with arrhythmia. Material/Methods: A total of 60 patients were separated into 2 groups: spinal block was applied with 10 mg bupivacaine to Group S1 and with 15 mg to Group S2. The mean arterial pressure (MAP) and heart rate (HR) values were recorded before the spinal block and at 5 and 30 min after the block and at 60 min postoperatively. By recording the time of the spinal sensory block to reach T10 dermatome (Anaesth T) and the duration of the surgical procedure (Surg T.), the QTc intervals were calculated. Results: The demographic data were similar in both groups. A statistically significant difference was determined between the S1 and S2 groups between the baseline and the 30 mins after spinal block QTc intervals (p=0.001). No statistically significant difference in HR values was determined between the groups at baseline, 5 min after spinal block, and 1 h after surgery (all p>0.05), but at 30 min after spinal block value there was a statistically significant difference (p= 0.010). No statistically significant difference was determined in MAP values between the groups at baseline and 1 h after surgery (p>0.05). Conclusions: The QTc interval lengthened in a dose-dependent manner after spinal anesthesia was applied with different doses of bupivacaine, but the doses used did not cause any severe arrhythmia.
Keywords: Anesthesia, Spinal; Arrhythmias, Cardiac; Bupivacaine; Long QT Syndrome